-38=3(y-6)-5y

Simple and best practice solution for -38=3(y-6)-5y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -38=3(y-6)-5y equation:


Simplifying
-38 = 3(y + -6) + -5y

Reorder the terms:
-38 = 3(-6 + y) + -5y
-38 = (-6 * 3 + y * 3) + -5y
-38 = (-18 + 3y) + -5y

Combine like terms: 3y + -5y = -2y
-38 = -18 + -2y

Solving
-38 = -18 + -2y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '2y' to each side of the equation.
-38 + 2y = -18 + -2y + 2y

Combine like terms: -2y + 2y = 0
-38 + 2y = -18 + 0
-38 + 2y = -18

Add '38' to each side of the equation.
-38 + 38 + 2y = -18 + 38

Combine like terms: -38 + 38 = 0
0 + 2y = -18 + 38
2y = -18 + 38

Combine like terms: -18 + 38 = 20
2y = 20

Divide each side by '2'.
y = 10

Simplifying
y = 10

See similar equations:

| 4x-3/2=-3/2x-6/5 | | -5-X/-3=-5 | | -8(5-3x)=2(x+11) | | s^2+4s+16=0 | | 3x+4+3x+3x+3=180 | | 6y+2=-2 | | (m^2)*x+1=m*x+m | | 5y-8=-38 | | Graphx=-1+-0.3333 | | 12X-3X+516=5+5X+15 | | 25=y-7 | | 8y-3=2(2y+8) | | 86x-13=5 | | 8x-5(x-2)=x+24 | | -7u-1/3=1/2u-5/4 | | 3y+3(8+4g)=1-g | | 8x^2+15x+c=0 | | 34+2x=42 | | -4/5=-1/2u-4/3 | | -18+20x=-9 | | 2(x-8)=3(x-5) | | 6/5-4y=-18 | | 12x+4=7x-26 | | 58000+1.20x=15x | | .4(4x+11)=3(3-2x)+3 | | 1800+.01x=.06x | | -6(4x-9)+4=-24x+58 | | y+5.5=0.5(y+3) | | 6(x+2)-5=15-2x-8+8x | | -2/3x-3/2=-9/5 | | 1.7(4-x)=-.07(7-x) | | -2+4(x-4)=13x+3-9x |

Equations solver categories